Experiential-Reflective Teaching Approach :Effects on Student Environmental Sensitivity and Decision-Making Skills - Guerrero, Charlaine G. (Alipato, A Journal of Basic Education, 2017)
In response to the environmental problems brought about by natural processes and human actions, development of man’s sensitivity  and better decisions concerning the environment must be one of the major foci of the educational system. However, the discussion of environmental concepts and issues is not given much emphasis in the new Philippine K to 12 Basic Education Curriculum. Experiential-Reflective Teaching Approach is an instructional approach combining the principles of experiential learning and reflective learning  in which teachers develop science lessons  through the process of utilizing and analyzing students’ experiences with the environment. The approach is implemented in line with the educational goals of the new educational curriculum as well as with the goal of environmental education through the integration of environmental issues in science teaching. It is composed of four sub-instructional activities namely, Experiential Activity, Individual Reflective Practice, Processing, and Decision-Making activity. The study aimed at assessing the effects of Experiential-Reflective Teaching Approach on environmental sensitivity and decision-making skills of Grade 6 students and determining if the first positively predicts the latter. The study was conducted to Grade 6 students in a public elementary school in Tarlac City. The study made use of two instruments: Environmental Sensitivity Scale and Decision-Making Test on Environmental Issues. Results of the independent samples t-test showed that Experiential-Reflective Teaching  Approach is an effective means of developing students’ environmental sensitivity and decision-making skills. Moreover, linear regression showed that student environmental sensitivity is not a significant positive predictor of student decision-making skills.